A polymerase chain reaction-based methodology to detect gene doping - Carter, A.; Flueck, M. (European Journal of Applied Physiology, 2012)
The non-therapeutic use of genes to enhance athletic performance (gene doping) is a novel threat to the World of Sports. Skeletal muscle is a prime target of gene therapy and we asked whether we can develop a test system to produce and detect gene doping. Towards this end, we introduced a plasmid (pCMV-FAK, 3.8 kb, 50 µg) for constitutive expression of the chicken homologue for the regulator of muscle growth, focal adhesion kinase (FAK), via gene electro transfer in the anti-gravitational muscle, m. soleus, or gastrocnemius medialis of rats. Activation of hypertrophy signalling was monitored by assessing the ribosomal kinase p70S6K and muscle fibre cross section. Detectability of the introduced plasmid was monitored with polymerase chain reaction in deoxyribonucleic acids (DNA) from transfected muscle and serum. Muscle transfection with pCMV-FAK elevated FAK expression 7- and 73-fold, respectively, and increased mean cross section by 52 and 16% in targeted muscle fibres of soleus and gastrocnemius muscle 7 days after gene electro transfer. Concomitantly p70S6K content was increased in transfected soleus muscle (+110%). Detection of the exogenous plasmid sequence was possible in DNA and cDNA of muscle until 7 days after transfection, but not in serum except close to the site of plasmid deposition, 1 h after injection and surgery. The findings suggest that the reliable detection of gene doping in the immoral athlete is not possible unless a change in the current practice of tissue sampling is applied involving the collection of muscle biopsy close to the site of gene injection.